2002
DOI: 10.1002/jcp.10061
|View full text |Cite
|
Sign up to set email alerts
|

Obesity modulates the expression of haptoglobin in the white adipose tissue via TNFα

Abstract: Increase in adipose mass results in obesity and modulation of several factors in white adipose tissue (WAT). Two important examples are tumor necrosis factor alpha (TNFalpha) and leptin, both of which are upregulated in adipose tissue in obesity. In order to isolate genes differentially expressed in the WAT of genetically obese db/db mice compared to their lean littermates, we performed RNA fingerprinting and identified haptoglobin (Hp), which is significantly upregulated in the obese animals. Hp is a glycopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 40 publications
2
65
0
5
Order By: Relevance
“…A genomic approach resulted in a similar finding, because haptoglobin mRNA was found to be significantly upregulated in the adipose tissue of obese rodents (2,3). Furthermore, haptoglobin is present at increased levels in the blood of obese humans (4,5).…”
mentioning
confidence: 65%
“…A genomic approach resulted in a similar finding, because haptoglobin mRNA was found to be significantly upregulated in the adipose tissue of obese rodents (2,3). Furthermore, haptoglobin is present at increased levels in the blood of obese humans (4,5).…”
mentioning
confidence: 65%
“…Indeed, it has been shown that the 4 Some of these are recognised as acute-phase proteins of inflammation (e.g. IL6, 5 C-reactive protein [CRP] 6 and haptoglobin 7,8 ). Furthermore, we have observed that different isoforms of the serum amyloid A (SAA) protein, usually known to be produced by the liver, can also be produced by the WAT.…”
Section: Origin Of Chronic Inflammation In Obesity and Contribution Omentioning
confidence: 99%
“…Because BMI correlates positively with oxidative stress (31), this finding supports the suggestion that differences in the antioxidative function of Hp phenotypes contribute to the development of GDM. Elevated serum levels of Hp found in GDM (Table 1) may reflect the higher BMI present in women with GDM, leading to increased expression of Hp in fat tissue (1). In fact, we observed a significant correlation between BMI and Hp levels, and no significant risk could be attributed to Hp levels in a multivariate risk model for GDM that included BMI.…”
Section: Metabolic Characteristicsmentioning
confidence: 61%
“…H aptoglobin (Hp) is an acute-phase protein synthesized in the liver and, to some extent, in fat tissue (1) in response to interleukin 6 -type cytokines. The Hp gene is located on the long arm of chromosome 16 (16q22.3) (2).…”
mentioning
confidence: 99%